(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
The current research tackles the Barriers that faced the Working of the Psychological Counselors in light of the Syrian Crisis at Schools "Second Cycle" of basic Education in Lattakia Governorate. Differences in their views on the Barriers that faced are attributed to the following variables (scientific and educational qualification, years of experience). In order to achieve the objective of the research, the descriptive method was used. The sample included (204) psychological counselors in Schools "Second Cycle" of basic Education in Lattakia Governorate for the academic year 2018/2019. The reached several results, the most important of which: - The total degree of Barriers that faced the Working of the Psychological Counselors in light of the Syrian Crisis at Schools "Second Cycle" of basic Education in Lattakia Governorate from their point of view came to a medium degree. - There were no statistically significant differences between the average estimation of the members of the research sample on the Barriers that faced their Working according to the variable years of experience. - There are statistically significant differences between the average of the assessment of the members of the research sample on the Barriers that faced their Working according to the scientific and educational qualification in favor of the post graduating. تناول البحث الحالي المعوقات التي تواجه عمل المرشدين النفسيين في ظل الأزمة السورية في مدارس الحلقة الثانية من التعليم الأساسي في محافظة اللاذقية، والتعرف إلى الفروق في المعوقات من وجهات نظرهم تبعاً للمتغيرات الآتية (عدد سنوات الخبرة، والمؤهل العلمي والتَّربوي). ولتحقيق هدف البحث اسُتخدم المنهج الوصفي، واشتملت عينة البحث على (204) مرشداً ومرشدة في مدارس الحلقة الثانية من التعليم الأساسي في محافظة اللاذقية للعام الدراسي (2018/2019). صممت استبانة احتوت على خمسة مجالات، وهي (المعوقات المدرسية، المعوقات الخاصة بالمرشدين النفسيين، المعوقات الخاصة بالإشراف التربوي للإرشاد النفسي، المعوقات الخاصة بالطلبة، المعوقات الخاصة بالمجتمع المحلي). توصل البحث إلى مجموعة من النتائج أهمها: • جاءت الدَّرجة الكليَّة للمعوقات التي تواجه عمل المرشدين النفسيين في ظل الأزمة السورية في مدارس الحلقة الثانية من التعليم الأساسي في محافظة اللاذقية من وجهة نظرهم بدَّرجة متوسطة. • لم تظهر فروق ذات دلالة إحصائية بين متوسطات تقدير أفراد عينة البحث حول المعوقات التي يواجهونها تبعاً لمتغير عدد سنوات الخبرة. • وجود فروق ذات دلالة إحصائية بين متوسطات تقدير أفراد عينة البحث حول المعوقات التي يواجهونها تبعاً لمتغير المؤهل العلمي والتَّربوي لصالح حملة الدراسات العليا.